KEPEMIMPINAN PEREMPUAN PERSPEKTIF MUFASSIR NUSANTARA - Tohet, Moch.; Maulidia, Lathifatul (JURNAL ISLAM NUSANTARA, 2018)
The phenomenon that occurred in the archipelago in the Modern Era as it is today, women have appeared to be "leaders" both in the domestic and public sphere. So that this becomes a problem of its own because they demand gender equality. So, this happened to the inner contradiction between the ideals of sharia and the phenomenon that occurred in the archipelago society. Based on the above problems, it is the main attraction for researchers to explore the thoughts of Mufassir Nusantara in relation to "Problems of Domestic and Public Women's Leadership" along with finding similarities and differences between their interpretations. The aim of this study is to transform the Islamic scientific nature of the archipelago so that it can contribute to Islamic thinking related to Nusantara and for the citizens of the Archipelago related to these problems.